Entre concubinage et prostitution. Processus d’exclusion dans le Costa Rica de la fin du xixe siècle - Marion Giraldou (Cahiers des Amériques Latines)
I understand my research subject – prostitution – not as "fact" but as social construct. Such a study requires to vary my approaches in order to focus not only on the study of such a social group itself but also on the relationships between this group and society. Several dynamics thus arise which establish a link between the commonly-shared opinion (at society level), the diffusion of cultural norms (at state level) and the resistance to homogenisation (regarding marginality). Following such a reasoning, this very article analyses the flexibility in the use of concepts such as concubinage and prostitution – indeed, these two forms of "unclassifiable" sexualities, although both answering a clear definition accepted by society, tend to overlap and become synonyms. Marginality therefore appears to be characterized not by pre-established definitions relying on certain criteria, but rather by a complex construct interweaving several mechanisms.